A family business perspective on emergence and potential of mass retail industry in India. Issue 4 (11th April 2016) - Prabhakar, Guru Prakash; Saran, Pankaj
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: This article helps to understand the mind-set and leadership qualities of leaders hailing from family-run businesses in India. Practical implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.